Antibacterial and sporicidal activity of Syzygium grande (Wight) Walp. and Oenanthe javanica (Blume) dc. against Bacillus sp. - Atrash, Khaled Abdusalam. B. A (2020)
The contamination of many products in the food industry has always been linked to spore-forming bacteria including Bacillus sp. which commonly found in different type of food raw materials. Although different approaches for managing bacterial endospore contamination is urgently needed in diverse industries and applications, natural products are seen as the alternative solution. Based on previous studies, both Syzygium grande and Oenanthe javanica have been reported to exhibit several biological properties including antibacterial and antifungal. Thus, the main aim of this study is evaluating antibacterial and sporicidal activities of Syzygium grande and Oenanthe javanica against vegetative cells and spores of B. cereus ATCC33019, B. subtilis ATCC6633, B. megaterium ATCC 14581 and B. pumilus ATCC 1488. A further objective is to isolate the bioactive compound(s). In this study, the metabolomics analysis of the 70% methanol, methanol, ethyl acetate and hexane extracts from the both plant was performed and showed clear discrimination between the different solvent extracts due to presence of different classes of compounds. Twenty compounds of S. grande have been assigned, including amino acids, carbohydrate, triterpene, terpenoids, and organic compounds. Compounds responsible for the differentiation were identified by comparison of their 1H-NMR chemical shifts. The PLS results indicated that many non-polar compounds from S. grande hexane extract included betulin, β-sitosterol, oleanolic acid, β- caryophyllene, acetic acid and 3-hydroxybutyric acid were strongly correlated to anti- Bacillus. While, eighteen compounds of O. javanica have been assigned, including amino acids, carbohydrate, an organic acid terpenoids, and organic compounds. The PLS results showed the different polar compounds included sugars, glycine, choline, proline, ellagic acid, and gallic acid from O. javanica methanol extract are the potential contributors for the antimicrobial activities. Various solvent fractions obtained from solvent partitioning of the methanolic extracts of S. grande and O.javanica were screened for antimicrobial and sporicidal activity against of target Bacillus species, respectively. The hexane fraction of both plant showed the highest antimicrobial and sporicidal activities against all Bacillus sp. The results showed that the growth of vegetative cells of all tested Bacillus species were inhibited by S. grande hexane fraction at 1.0% with MIC values ranged between 0.039 to 0.625 mg/mL. While, MBC values ranging between 0.312 to 1.25 mg/mL. Bacillus species was also inhibited by O. javanica hexane fraction with MIC between 0.078 to 0.625 mg/mL. While, MBC values between 0.625 to 2.5 mg/mL. From time-kill assays, 4×MIC and 8×MIC of the hexane fractions of S. grande and O. javanica, respectively, were found to kill 99.90% of Bacillus sp. after 2 to 4 h incubation. Hexane fraction of S. grande was found to completely eradicate all Bacillus spores at 1%, after 2 to 3h of incubation. Similarly, O. javanica hexane fraction completely eradicate of all Bacillus spores at 1% after 3 to 4h of incubation. From the GCMS analysis, a total of 33 and 29 compounds could be putatively identified in the S. grande and O. javaneca hexane fractions, respectively, which included hydrocarbons, fatty acid, diterpenoids and triterpenoids. Meanwhile, 18 compounds from S. grande and 21 compounds from O. javanica ethyl acetate fractions were putatively identified using LC-MS/MS analysis. Most of the compounds had antibacterial activities based on previously reported. Isolation of bioactive constituents was then attempted on the active fractions using bioautographic assay and column chromatography. The hexane fraction of S. grande yielded β-sitosterol and ursolic acid, while lupeol was isolated from the hexane fraction of O. javanica. All compounds were found able to inhibit the growth of all the Bacillus species at 100 μg/mL. Both β-sitosterol and lupeol gave lowest MIC value (31.25 μg/mL) against B. pumilus, and gave equally low MIC values (31.25 to 62.5 μg/mL) against the other Bacillus species. Overall the MBC values ranged from 125 to 250 μg/mL. While, ursolic acid was slightly less bioactive, with MIC values of 62.5 to 250 μg/mL against the test organisms, while the MBC values ranged from 125 to 500 μg/mL. Finally, at concentrations 100 to 1000 μg/mL, the three compounds were investigated for their abilities to reduce the viability of Bacillus sp. spores. β- sitosterol was found to kill all Bacillus spores at 1000 μg/mL, after 2 to 3 h of incubation while, ursolic acid at same concentration was killed all Bacillus spores after 2 h of incubation. Similarly, lupeol at 1000 μg/mL, gave complete elimination of Bacillus spores after 1 or 2 h of incubation. In conclusion, S. grande and O. javanica hexane fractions and its compounds which isolated from these fractions exhibited antimicrobial and sporicidal activity against Bacillus species, thus it can be developed as anti-Bacillus agent.